Examining the role of anti-slip socks in enhancing balance and stability among university futsal players / Muhammad Rifdi Mohd Rosli ... [et al.]. - Mohd Rosli, Muhammad Rifdi; Shari, Maisarah; Mohamed, Muhamad Noor; Saiful Annur, Muhamad Safiq; Mazaulan, Mardiana; Adnan, Mohd Aizzat; Abu Kassim, Nurul Ain; Raja Hussain, Raja Nurul Jannat; Md Radzi, Noor Azila Azreen (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Balance is crucial for futsal players, yet the role of anti-slip socks in enhancing balance performance remains underexplored. Agility and dynamic balance were significantly better using grip socks compared to those wearing standard socks [1]. Most existing research focuses on external supports like taping, bracing, and orthoses, with little attention to the potential benefits of grip socks [2]. This research investigates the effect of grip socks on balance among UiTM futsal players, addressing gaps in understanding their potential to improve stability and reduce injury risks, particularly when compared to standard socks. A quantitative experimental design involved 24 UiTM futsal players (19–24 years). Static and dynamic balance were assessed using the Balance Error Scoring System (BESS) and Star Excursion Balance Test (SEBT). Grip socks with standardized soles were compared to regular socks under randomized conditions. Paired t-tests analyzed performance differences, with significance set at p<0.05.